The diagnostic significance of hyperfibrinogenemia and thrombocytosis in patients with ovarian tumors/adnexal masses - Sontakke, Bhavana; Arora, Ruchi; Patel, Shilpa M.; Parekh, Chetana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: We aim to study the correlation of thrombocytosis and hyperfibrinogenemia with ovarian tumors and its role in the diagnosis of ovarian malignancy. And to evaluate the platelet and fibrinogen levels in early and advanced stage ovarian disease. Methods: This is a single centre prospective study. We evaluated plasma fibrinogen levels and plasma platelet levels in 250 patients in women presenting in our OPD with adnexal masses/ovarian tumors. Thrombocytosis was defined as a platelet count greater than >410,000/uL. Hyperfibrinogenemia was defined as a fibrinogen level higher than 360 mg/dL. The association between plasma fibrinogen, platelet levels and clinico-pathological, histopathological parameters were investigated in regards to: 1. Malignant or benign ovarian tumor. 2. Early or advanced disease in malignant ovarian tumors. A multivariate logistic regression model was performed to identify an independent association. Results: Thrombocytosis and hyperfibrinogenemia are seen to be associated with malignant ovarian tumors. In a multivariate model, plasma fibrinogen and plasma platelet levels were identified to be independently associated with the malignant ovarian tumours. Within the EOC cohort, patients with advanced stage disease had higher plasma fibrinogen levels than patients with early stage. Conclusions: In this study, we demonstrated that both thrombocytosis and hyperfibrinogenemia were positively associated with malignant ovarian tumors. They were also associated with advanced disease stage, elevated CA125 level and other markers. These finding are in accordance with the previous published data from patients with ovarian cancer, indicating that the platelet and fibrinogen levels increase in parallel with tumor progression and metastasis. Thus confirming the role of elevated platelet and fibrinogen levels in diagnosis and prognosis of ovarian Malignancy.